The Effectiveness of Mobile Application as an Alternative of Health Education Media for Adolescents in the Middle School - Noordiati1 , Erina Eka Hatini1 , Greiny Arisani1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Adolescent health problems are still becoming major issues in health issues such as smoking behavior, drugs, and free sex. Improving health school age and adolescent is prioritized in promotive and preventive efforts. One of them is done through the school health effort. The purpose of this study was to determine the effectiveness of mobile applications as a health education media for adolescents in secondary schools towards adolescent knowledge and attitudes about health, compared to printed media. This type of research is quasi experimental research with a two group comparison pretest-posttest design. There were significant mean differences in knowledge, attitudes and skills before and after getting an intervention using the mobile application media (p = 0.000). There were significant mean differences in knowledge, attitudes and skills before and after getting an intervention using the My Health Report Card (p = 0.000). There was a significant mean difference in knowledge, where the mean score of knowledge was higher in the group using the mobile application media compared to using the My Health Report Card (p = 0.000). There are no differences in the attitudes and attitudes of groups who use the mobile application media and who use the My Health Report Card.